2007
DOI: 10.1186/1471-2458-7-175
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the General Health Questionnaire (GHQ-12) in subjects who had suffered from the 2004 Niigata-Chuetsu Earthquake in Japan: a community-based study

Abstract: Background: Factor structure of the 12-item General Health Questionnaire (GHQ-12) was studied by a survey of subjects who had experienced the 2004 Niigata-Chuetsu earthquake (6.8 on the Richter scale) in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…The few studies examining the subset of Functioning symptoms in trauma-affected populations have found similar results. For example, Toyabe et al (2007) found low Functioning scores among a community sample of Japanese adults 2 years after experiencing the Niigata-Chuetsu earthquake. In a household survey of Kosovar Albanians after the Kosovo war, Lopes Cardozo et al (2000) found poor levels of social functioning measured by the GHQ 28-item version.…”
Section: Discussionmentioning
confidence: 95%
“…The few studies examining the subset of Functioning symptoms in trauma-affected populations have found similar results. For example, Toyabe et al (2007) found low Functioning scores among a community sample of Japanese adults 2 years after experiencing the Niigata-Chuetsu earthquake. In a household survey of Kosovar Albanians after the Kosovo war, Lopes Cardozo et al (2000) found poor levels of social functioning measured by the GHQ 28-item version.…”
Section: Discussionmentioning
confidence: 95%
“…The psychological stress after a largescale disaster, such as an earthquake, continues for a long period (7,8). Furthermore, the burden on the caregivers at nursing homes in Japan was already problematic before the disaster (9-11) because of long working hours and low pay, which led to a shortage of such caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Developed as a screening instrument for psychological distress in the general population, the GHQ-12 has also been frequently used to assess psychological distress in survivors of large disasters [21]. In subjects who had experienced the Niigata-Chuetsu earthquake, the GHQ-12 was higher at 5 months [34] and 2 years after the earthquake [78], predicting an impaired recovery in the ability to cope with daily problems.…”
Section: Discussionmentioning
confidence: 99%